Dykha O.V., Stebeletska N.M., Dynko O.P. Composite lubricants in sliding tribosystems of machines. - Диха, О. В.; Стебелецька, Н. М.; Динько, О. П. (Problems of Tribology, 2018)
In this study, an analysis of the results of studies on the effects of various antifriction and anti-wear additives on lubricants on the tribological properties of the surface layers of machine parts. The prevailing mechanisms of the action of additives to reduce the resistance to movement and to reduce wear and tear of friction surfaces in the process of contact interaction are determined.